DAMPAK PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, DAN BELANJA MODAL BAGI PERTUMBUHAN EKONOMI - Eva, Helena (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to determine the effect of regional original income, balancing funds, and capital expenditures both partially and jointly on the economic growth of Ngawi Regency in 2006 – 2021. This type of research is quantitative because it uses statistics to test hypotheses. This study uses 16 annual time series data for each variable. The sampling technique uses purposive sampling. Data analysis using multiple linear regression. The results of the study found that regional original income had a real impact on economic growth. Balancing funds have a real impact on economic growth. Capital expenditure is one of the factors that can have a real impact on economic growth. Regional adli revenues, balancing funds, and capital expenditures affect the economic growth of Ngawi Regency in 2006 - 2021.